Exogeneity tests for the Chinese and U.S. external balance: Empirical evidence of the connection and the subprime crisis - Luiz Antônio de Lima Junior; Cláudio Roberto Foffano Vasconcelos; Wilson Luiz Rotatori Corrêa; José Sim\~ao Filho (EconomiA, 2014)
This paper studies the global imbalances that occurred in the first years of the twenty-first century. The analysis encompasses the two biggest countries in the world: the U.S.A. and China. Many authors defend the assertion that the relationship between the current accounts of these two countries was one important cause of the subprime crisis. While the U.S.A. has increased its deficit in the last decade, China has improved its surplus. To investigate this relationship, this study performed exogeneity tests. Moreover, it conducted Granger causality tests following the approach of Toda–Yamamoto (1995). The results showed that there is a real causal relationship between the American and the Chinese external balance. Furthermore, the global imbalance between these two countries contributed to the subprime crisis, because the tests detected structural breaks for the external balances of America and China in 2008. The dynamics of the Chinese external balance changed after the subprime crisis. – – Este trabalho estudou a dinâmica da relaç\~ao entre o saldo externo chinês e o saldo externo norte-americano nos primeiro anos do século XXI. O estudo desta dinâmica se justifica uma vez que a mesma é apontada por muitos autores como uma das causas da crise subprime, ocorrida em 2008. Com a finalidade de estudar esta dinâmica foram usados os testes de exogeneidade para investigar a existência da relaç\~ao entre o saldo externo destes dois países. A investigaç\~ao desta relaç\~ao foi dada por meio da abordagem de Toda–Yamamoto (1995). A conclus\~ao que este trabalho chegou foi que o desequilíbrio macroeconômico entre China e EUA tem uma relaç\~ao causal. Além disso, estes desequilíbrios est\~ao relacionados com a crise de 2008, uma vez que foram detectadas quebras estruturais para o saldo externo dos dois países no ano de 2008 e a dinâmica do saldo em transaç\~oes correntes do saldo externo chinês se modificou após a crise subprime.
Keywords: F40; F32; E20; 330; Exogeneity test; External balance; Macroeconomic imbalance